Factors Affecting The Persistence And Academic Performance Of OMSC Faculty And Employees In Seeking Master’s Degree - Escultor, Marites D.; Linda L. Pelayo, Leiza (International Journal of Educational Research & Social Sciences, 2022)
Pursuing graduate studies is an important decision in life that should not be taken lightly. The study identified factors that affects the persistence of graduate students in pursing Master’s degree on either through scholarship grants or self-expense study. Using a survey questionnaire online thru google forms, 136 respondents answered back. The result of the study found that majority of the respondents are female and 66% of the respondents finished their master’s degree. Institutional factors like expertise of the faculty was very important to respondents are important to the graduate students. While the academic performances are affected by positive factors like support of the family and friends, negative factors like poor time management and work overload, 69% the respondent’s GPA is 2.0 and above which indicates good performance in graduate school.